Diamond Radiation Detector with Built‐In Boron‐Doped Neutron Converter Layer. Issue 3 (20th October 2021) - Miyake, Taku; Nakagawa, Hisaya; Masuzawa, Tomoaki; Yamada, Takatoshi; Nakano, Takayuki; Takagi, Katsuyuki; Aoki, Toru; Mimura, Hidenori
Abstract : Herein, a radiation detector made of polycrystalline diamond with a boron (B)‐doped neutron converter layer is presented. The detector is fabricated by the hot filament chemical vapor deposition technique, and consists of an undoped free‐standing polycrystalline diamond layer and a B‐doped polycrystalline diamond top layer that serves as an electrical contact and a converter for neutron‐alpha conversion. Characterization of the diamond films and detector operation is presented. The results indicate that the B‐doped layer acts as an effective neutron‐alpha converter, whereby neutron detection is demonstrated in particle‐counting mode using a multichannel analyzer. Abstract : A radiation detector made of polycrystalline diamond with a boron (B)‐doped neutron converter layer is proposed and fabricated. The B‐doped layer is confirmed to work as an effective neutron‐alpha converter, whereby converted particles are detected as an electrical signal via an undoped diamond layer. Neutron detection is successfully demonstrated in particle‐counting mode, suggesting a possibility of a polycrystalline diamond radiation sensor for wide‐area flat panel detector.